Retorikang Filipino Pang-antas tersyaryo - Bisa, Simplicio P. (Malate, Manila De La Salle University Press, 1998)
Grammar of Tagalog language of the Philippines.
Includes bibliographical references (p. 137-138).
High School to College Studdent
In Tagalog.
Keywords: Tagalog language -- Grammar